Multi objective Fuzzy programming of remanufactured green perishable products using supply contracts - Khalafi, Sepideh; Hafezalkotob, Ashkan; Mohammaditabar, Davood; Sayadi, Mohammad Kazem (International journal of management science and engineering management, 2020)
In the recent times, remanufacturing and recycling processes have been widespread because of hard environmental legislations. The significance of green factors such as uncertainty of return rates in supply networks has been extensively acknowledged in presented studies. A revenue sharing contract improves the performance of green supply chain and has a significant role in the profitability of total supply chain. There are few quantitative studies on revenue sharing contract in green supply chains. In this study, we propose coordination subject matters of a green supply chain with recycling perishable goods, involving suppliers, manufacturers, retailers, together with collection and disposal centers, in a multi-product, multi-period and multi-level basis under Fuzzy conditions. The consequences indicate that in dairy industries, appropriate collected returned products could be used as raw material for another product, which increases the supply chain profits and reduces waste; and also, since perishable goods have a limited shelf life, they can be reusable if they are collected before reaching to a critical time. Furthermore, the proposed revenue sharing contract can share benefits between supply network members and gain coordination of channel.